PENGARUH KEAHLIAN, PENGALAMAN, KOMPLEKSITAS TUGAS DAN INDEPENDENSI TERHADAP AUDIT JUDGEMENT AUDITOR INTERNAL PADA INSPEKTORAT PROVINSI GORONTALO - Alamri, Fitria; Nangoi, Grace B.; Tinangon, Jantje (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
ABSTRACT. One of the functions of the inspectorate as mandated in Article 4 of Regulation of the Minister of home Affairs Number 64 Year 2007 is to carry out the examination. In the process of examination of the regulatory authorities to gather evidence that wii be evaluated of the findings and recommendations. At the time of issuing the auditor's recommendations requires judgment which is the opinion or judgement of the auditor based on evaluation of evidence. This  study aims to empirically examine the influence of the expertise, the experience, the complexity of the tasks and the independence of the audit judgment. This study uses quantitative methods. Samples from this study is the auditor and the auditor has a certificate in the Inspectorate of Gorontalo Province. The data used in this study are primary data using questionnaires to respondents were 63 questionnaires. Data analysis methods used to test the hypothesis is multiple linear regression analysis were processed with SPSS 13. The results partially (t test) indicates that the variable expertise and experience no significant effect on audit judgment, while the complexity of the task and the independence of positive and significant impact on audit judgment auditor at the Inspectorate of Gorontalo Province.Keywords: expertise, experience, task complexity, independence, audit judgments